2016
DOI: 10.3390/v8120323
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteome Analysis of Porcine Jejunum Tissues in Response to a Virulent Strain of Porcine Epidemic Diarrhea Virus and Its Attenuated Strain

Abstract: Porcine epidemic diarrhea virus (PEDV), a predominant cause of acute enteric infection, leads to severe dehydrating diarrhea and mortality in piglets all over the world. A virulent PEDV YN13 strain, isolated in our laboratory, was attenuated to yield an attenuated PEDV strain YN144. To better understand the pathogenesis mechanism and the virus-host interaction during infection with both PEDV YN13 and YN144 strains, a comparative proteomic analysis was carried out to investigate the proteomic changes produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…YN13 and YN144 strains were obtained by passaging the YN strain, a variant strain isolated from the intestine of a piglet with diarrhea, for 13 and 144 generations, respectively. Our previous study has demonstrated that YN13 was a virulent strain and YN144 was an attenuation strain [ 20 ]. CV777 strain, a classical PEDV strain, was provided by Chengdu Tecbond Biological Product Co., Ltd. (Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…YN13 and YN144 strains were obtained by passaging the YN strain, a variant strain isolated from the intestine of a piglet with diarrhea, for 13 and 144 generations, respectively. Our previous study has demonstrated that YN13 was a virulent strain and YN144 was an attenuation strain [ 20 ]. CV777 strain, a classical PEDV strain, was provided by Chengdu Tecbond Biological Product Co., Ltd. (Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Details of this part have been described in our previous study [ 20 ]. Briefly, twelve piglets were randomly divided into three groups of four.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock protein 27 (HSP27) belongs to the small heat shock proteins family, which has been identified as a multifunctional protein involved in cytoskeletal stability, proinflammatory processes, and the inhibition of apoptosis [222,223]. Several HSPs have been reported to be implicated in PEDV infection in vitro and in vivo [224,225]. Indeed, the infection of many viruses up-regulates HSP27 expression by different mechanisms to delay cellular apoptosis, then supplies sufficient time for viral replication [226,227].…”
Section: Pedv Inhibits Heat Shock Protein 27 Expression To Impair Innmentioning
confidence: 99%
“…PEDV infections are more frequent in the winter [3], and although PEDV can infect swine of all ages, it causes the most serious harm to suckling piglets. Since the discovery of PED in England in 1971, the disease has expanded to many countries in Europe and Asia, especially China and South Korea, which has caused huge economic losses [4]. In China, PEDV is widely distributed, and outbreaks have a strong negative impact on the swine industry, in part due to the acute onset and fast spread of the virus,the incidence rate in piglets can be very prevalent [5][6][7].…”
Section: Introductionmentioning
confidence: 99%